Taxonomy and molecular systematics of three oligotrich (s.l.) ciliates including descriptions of two new species, Strombidium guangdongense sp. nov. and Strombidinopsis sinicum sp. nov. (Protozoa, Ciliophora). Issue 5 (2nd September 2016) - Liu, Weiwei; Xu, Dapeng; Ma, Honggang; Al-Farraj, Saleh A.; Warren, Alan; Yi, Zhenzhen
Abstract : In this study we investigated the morphology of three oligotrich (s.l.) ciliates, Strombidium guangdongense sp. nov., Cyrtostrombidium paralongisomum Tsai et al., 2015 and Strombidinopsis sinicum sp. nov. Strombidium guangdongense sp. nov. is characterized by its elongate obconical to obovoidal body shape and widely spaced dikinetids in the girdle and ventral kineties. Another new species, Strombidinopsis sinicum sp. nov. is diagnosed by its small size and semi-globular body shape without mineral envelopes. Some additional morphological data of the recently described species Cyrtostrombidium paralongisomum Tsai et al., 2015, such as the endoral membrane, are supplied based on our population. We also analysed the molecular phylogeny of each species based on small subunit rRNA (SSU rRNA) gene sequence data. The monophyly of Cyrtostrombidium is supported by our phylogenetic analyses, but the monophyly of Strombidinopsis and of the family Strombidinopsidae are both rejected by AU tests. In addition, Strombidium species have a tail branch separately from one another in phylogenetic trees, whereas strombidiids with a pigment spot group together, suggesting the latter character is a synapomorphy for this group of strombidiids. http://zoobank.org/urn:lsid:zoobank.org:act:35FE2AFD-A582-4885-BD01-48901E4C76C4 http://zoobank.org/urn:lsid:zoobank.org:act:E9D4A497-DAD6-4AA0-A044-A5A1D2C1A057